JURIDICAL REVIEW OF COMMERCIAL USE OF SONG CREATIONS IN RESTAURANTS/CAFES IN THE GOVERNMENT REGULATION NO. 56 OF 2021 ON SONG COPYRIGHT ROYALTIES AND/OR MUSIC - Yati Nurhayati; Christine Vina Siangli Putri; Muhammad Aini (Scholar Center, 2021)
Copyright is a part of intellectual property rights as a result of one's thoughts. Songs are a part of a copyright’s type that has received legal protection from acts harming the songwriter as stipulated in Law No. 28 of 2014 concerning Copyright. Everyone or a business activity such as a restaurant/café is allowed to use a song from a songwriter commercially in public service provided that it meets the specified requirements and mechanisms and the royalties are paid. However, based on the juridical-normative review, both Law No. 28 of 2014 and Government Regulation No. 56 of 2021 do not explain the understanding of commercial use of songs and regarding royalty payment procedures, this issue certainly requires legal certainty. The results showed that First, Government Regulation No. 56 of 2021 has determined the commercial use of songs in public services. But it does not specify and explain the purpose of commercial use of songs in public service, it needs to be clearly regulated for legal certainty. Second, Government Regulation No. 56 of 2021 has determined that everyone, singing songs commercially in public service, must pay royalties. But it is not specified about royalty payment procedures, this needs to be clearly regulated for legal certainty. This research aims to find out how to use songs commercially in Government Regulation No. 56 of 2021 regarding Song copyright royalties and/or music, how to pay royalties based on procedures for the commercial use of songwriting in Government Regulation No. 56 of 2021 concerning Song and/or Music Copyright Royalties. This research used normative legal research – research on secondary data comprising primary, secondary and tertiary legal materials collected through literature review.